2022
DOI: 10.1136/bmjopen-2021-058622
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the governance and preparedness of the Lebanese health system for the COVID-19 pandemic: a qualitative study

Abstract: ObjectivesThis study aimed to assess the capacities and governance of Lebanon’s health system throughout the response to the COVID-19 pandemic until August 2020.DesignA qualitative study based on semi-structured interviews.SettingLebanon, February–August 2020.ParticipantsSelected participants were directly or indirectly involved in the national or organisational response to the COVID-19 pandemic in Lebanon.ResultsA total of 41 participants were included in the study. ‘Hardware’ capacities of the system were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In future studies this must be accounted for, as it highlights the importance of overcoming such barriers, maybe through strategic use of even more local partnerships. Lebanon’s healthcare system exhibits a promising capacity for adaptation [ 30 ]. During our study, the staff showed a commendable willingness to adopt and maintain new practices.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies this must be accounted for, as it highlights the importance of overcoming such barriers, maybe through strategic use of even more local partnerships. Lebanon’s healthcare system exhibits a promising capacity for adaptation [ 30 ]. During our study, the staff showed a commendable willingness to adopt and maintain new practices.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the economic crisis on Lebanon's healthcare system also includes the loss of frontline healthcare professionals as well as the government's diminishing allocation for healthcare due to fiscal constraints [19]. These difficulties resonate across the healthcare system and jeopardize the availability and quality of critical medical treatments.…”
Section: Post‐pandemic Periodmentioning
confidence: 99%
“…The results show that “close collaboration between the government and the community,” “strict control of population movement,” and “massive deployment of nucleic acid testing points and medical facilities” are the keys to Guangzhou’s success in facing the sudden epidemic. Moussallem et al ( 9 ) conducted an evaluation of MPHPP in Lebanon in the form of a qualitative study based on semi-structured interviews. The results show that “health financing,” “medical human resources,” and “government governance capabilities” are critical for areas with severe political and economic pressure.…”
Section: Literature Reviewmentioning
confidence: 99%